Susanne B. Wilson and another woman sitting at a table - Unknown:::Creator::::::::::::
Photograph shows Susanne B. Wilson sitting at a table with another women. The table is set for a meal and has a decorative fan as a centerpiece. In the background there is a man at a podium with a large world map on the wall behind him. The map reads: "The world mission of the Methodist Church."